2015
DOI: 10.2355/isijinternational.isijint-2015-039
|View full text |Cite
|
Sign up to set email alerts
|

Phase-field Simulation of Habit Plane Formation during Martensitic Transformation in Low-carbon Steels

Abstract: The origin of the habit plane of the martensite phase (α ′) in low-carbon steels is elucidated by threedimensional phase-field simulations. The cubic → tetragonal martensitic transformation and the evolution of dislocations with Burgers vector a α ′ /2〈111〉 α ′ in the evolving α ′ phase are modeled simultaneously. By assuming a static defect in the undercooled parent phase (γ ), we simulate the heterogeneous nucleation in the martensitic transformation. The transformation progresses with the formation of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Anisotropy, the habit is a constant plane, which is consistent with the classic WLR and BM theory . In the last few decades, the phase field method has shown tremendous capabilities of predicting Martensitic phase transformation . When the martensite transformation model is solved based on the phase field method, the values of various parameters will directly affect the final calculation results.…”
Section: Introductionsupporting
confidence: 72%
“…Anisotropy, the habit is a constant plane, which is consistent with the classic WLR and BM theory . In the last few decades, the phase field method has shown tremendous capabilities of predicting Martensitic phase transformation . When the martensite transformation model is solved based on the phase field method, the values of various parameters will directly affect the final calculation results.…”
Section: Introductionsupporting
confidence: 72%
“…Later, the phase-field modeling of lath martensite formation in low-carbon steels, which is different from the above-mentioned models, 80,82) was developed by Murata and co-workers. [83][84][85][86][87] They proposed a new theory of plastic accommodation in the martensitic transformation by considering the slip deformation in the martensite phase, which was named the "two types of slip deformation" (TTSD) model. Using the TTSD model, it was shown theoretically for the first time that the hierarchical structures of lath martensite and the KS variants are formed as a result of slip deformation in the martensite phase.…”
Section: Martensitic Transformationmentioning
confidence: 99%
“…5, Tsukada et al demonstrated that the elastoplastic phase-field model based on the TTSD model reproduces the formation of a (111) habit plane during lath martensite formation. 85) Subsequently, the phase-field model was also applied to the modeling of lath martensite recovery. 87) In the future, further development of the phase-field model is expected for the quantitative prediction of not only lath martensite formation, but also other martensite morphologies in polycrystalline austenite.…”
Section: Martensitic Transformationmentioning
confidence: 99%
“…As mentioned above, the morphology of the lath martensite can be characterized by the plastic deformation accompanying dislocation slips, indicating that the maximum dislocation density is evaluated from the plastic strain caused by martensitic transformation. During the transformation, the dislocation density is considered to involve dislocations existing in the austenite phase around the martensite phase because if plastic strain arises in the austenite phase around the transformed martensite phase, the constraint force from the surrounding austenite phase to the newly formed martensite phase decreases, thereby decreasing the plastic strain in the newly formed martensite phase 56) . In other words, the total strain caused by martensitic transformation corresponds to the value in Fig.…”
Section: Dislocation Density Of Lath Martensitementioning
confidence: 99%